2006
DOI: 10.1021/ol060481c
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine−Thiourea as a Bifunctional Organocatalyst:  Highly Enantioselective Michael Addition of Cyclohexanone to Nitroolefins

Abstract: [reaction: see text] Asymmetric Michael additions of cyclohexanone to both aryl and alkyl nitroolefins in the presence of 20 mol % of organocatalyst 2b and 10 mol % of n-butyric acid afford adducts 5 with high diastereoselectivities and enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
106
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(113 citation statements)
references
References 24 publications
4
106
0
Order By: Relevance
“…Homogeneous cooperativity has been studied using multiple small molecules [3][4][5] or polyfunctional molecular catalysts. [6][7][8] Numerous examples have also been reported of inorganic cooperativity in heterogeneous catalysts by incorporating multiple different metal centers onto a support. Here, we focus exclusively on cooperativity among organic sites on the surface of a heterogeneous catalyst (with a specific focus on silica-supported organic groups).…”
Section: Cooperative Catalysismentioning
confidence: 99%
“…Homogeneous cooperativity has been studied using multiple small molecules [3][4][5] or polyfunctional molecular catalysts. [6][7][8] Numerous examples have also been reported of inorganic cooperativity in heterogeneous catalysts by incorporating multiple different metal centers onto a support. Here, we focus exclusively on cooperativity among organic sites on the surface of a heterogeneous catalyst (with a specific focus on silica-supported organic groups).…”
Section: Cooperative Catalysismentioning
confidence: 99%
“…[4][5][6] In particular, bifunctional amine-thiourea-based catalysts have proved to be efficient in various asymmetric transformations owing to the ability of the thiourea moiety to highly activate carbonyl or nitro groups through double hydrogenbonding interactions. 7,8 Therefore, this kind of organocatalyst has been widely studied in [12][13][14][15][16][17][18][19][20][21][22] Since Tsogoeva 23 and Jacobsen 24 demonstrated that a primary amine-thiourea catalyst can act as efficient bifunctional catalyst for the asymmetric nitro Michael addition, such bifunctional organocatalysts have attracted much attention owing to their easy preparation from chiral diamines. [25][26][27][28][29][30][31][32] However, the chiral scaffold of these reported organocatalysts is limited and is mostly derived from 1,2-diaminocyclohexane and 1,2-phenylethylenediamine.…”
Section: Introductionmentioning
confidence: 99%
“…A related study by Enders showed a strong solvent effect in the reaction since in MeOH the enantioselectivity could be increased to 76% for the major syn diastereomer in the reaction between 3-pentanone and trans-β-nitrostyrene employing a 20 mol% of Lproline as catalyst. [7] Since these preliminary studies, very effective catalytic systems (2-20) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] have been developed for the asymmetric Michael reaction of ketones with nitroalkenes being the process generally syn-selective (Scheme 1). Best improvements to this reaction have been mostly achieved using pyrrolidine-based catalytic derivatives.…”
Section: Introductionmentioning
confidence: 99%